2014
DOI: 10.1186/s40166-014-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient computer operation for users with a neuromuscular disease with OnScreenDualScribe

Abstract: We developed a tool based on a modified number pad to empower persons with certain diseases, in particular of neuromuscular origin, to efficiently operate a computer and enter text. As the keypad lies securely in both hands, the system is ideal for someone who has motor problems using a full-size keyboard. The software offers various assistive techniques. For example, text entry is facilitated with the help of word prediction, and an ambiguous mode with word-level disambiguation allows text entry using the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…All these parameters should be taken into account when working with NMDs. In a survey with NMD patients regarding the desired BCI features priorities, it was found that 63% of the subjects currently use a computer while the rest have stopped ( 13 , 14 ). No information was supplied regarding the preferred computer type or the operating system.…”
Section: Introductionmentioning
confidence: 99%
“…All these parameters should be taken into account when working with NMDs. In a survey with NMD patients regarding the desired BCI features priorities, it was found that 63% of the subjects currently use a computer while the rest have stopped ( 13 , 14 ). No information was supplied regarding the preferred computer type or the operating system.…”
Section: Introductionmentioning
confidence: 99%
“…Text input on mobile devices equiped with touch screens as the primary input device can be difficult, but is relevant to language learning tasks. This general problem led to the development of several alternative input methods (Ward et al, 2002;Kumar et al, 2012;Felzer et al, 2014;Shibata et al, 2016) including Ljunglöf's method of grammar-backed word-based text editing (2011).…”
Section: Introductionmentioning
confidence: 99%